The Effect of Student’s Perception of Learning Innovation on Student Engagement and Student Satisfaction - Anita Setyawati; Serli Wijaya; Deborah C. Widjaja (Master of Management, School of Business and Management, Petra Christian University, 2022)
The COVID-19 pandemic has changed how people live, including education. Due to an increase in positive cases of COVID-19, the teaching and learning process must be carried out online. However, online learning that is carried out suddenly caused by the pandemic can affect a decrease in student engagement and student satisfaction. This research aims to determine student perceptions of teaching innovations that impact student engagement and satisfaction. The online survey was distributed to 166 students of an international program at a private university in Surabaya, Indonesia. The research found that learning methods or strategies prepared by the lecturers to create learning innovation positively impact student engagement and student satisfaction. The ideal teaching method or strategy during online learning supports the interaction between the lecturer and students. Such interaction would increase student engagement, such as learning motivation, being confident in their abilities and deep understanding, and sharing learning experiences, ideas, and knowledge so that student satisfaction will be enhanced.